High-dose irradiation in combination with non-ablative low-dose radiation to treat metastatic disease after progression on immunotherapy: Results of a phase II trial. (September 2021) - Patel, Roshal R.; He, Kewen; Barsoumian, Hampartsoum B.; Chang, Joe Y.; Tang, Chad; Verma, Vivek; Comeaux, Nathan; Chun, Stephen G.; Gandhi, Saumil; Truong, Mylene T.; Erasmus, Jeremy J.; Hong, David S.; et al.
Highlights: HD-RT ± LD-RT to separate lesions can be safely delivered for IO refractory patients. HD-RT + LD-RT safely improved lesion-specific response for IO refractory patients. LD-RT may be a consideration for large tumors or multiple isocenters. T- and NK cell infiltration was enhanced in lesions treated with LD-RT. Abstract: Aim: To report early findings from a phase II trial of high-dose radiotherapy (HD-RT) with or without low-dose RT (LD-RT) for metastatic cancer. Methods: Eligible patients had metastatic disease that progressed on immunotherapy within 6 months. Patients were given either HD-RT (20–70 Gy total; 3–12.5 Gy/f), or HD-RT + LD-RT (0.5–2 Gy/f up to 1–10 Gy total) to separate lesions, with continued immunotherapy. Radiographic response was assessed per RECIST 1.1 and Immune-Related Response Criteria (irRC). Primary endpoints: (1) 4-month disease control (DCR, complete/partial response [CR/PR] or stable disease [SD]) or an overall response (ORR, CR/PR) at any point in ≥10% of patients, per RECIST 1.1; (2) dose-limiting toxicity within 3 months not exceeding 30%. Secondary endpoint was lesion-specific response. Results: Seventy-four patients (NSCLC, n  = 38; melanoma n  = 21) were analyzed (39 HD-RT and 35 HD-RT + LD-RT). The median follow-up time was 13.6 months. The primary endpoint was met for 72 evaluable patients, with a 4-month DCR of 42% (47% [16/34] vs. 37% [14/38] in HD-RT + LD-RT vs. HD-RT, P  = 0.38), and 19% ORR at any time (26% [9/34] vs. 13% [5/38] in HD-RT + LD-RT vs. HD-RT, P  = 0.27). Three patients had toxicity ≥grade 3. LD-RT lesion response (53%) was improved compared to nonirradiated lesions in HD-RT + LD-RT (23%, P  = 0.002) and HD-RT (11%, P  < 0.001). T- and NK cell infiltration was enhanced in lesions treated with LD-RT. Conclusions: HD-RT plus LD-RT safely improved lesion-specific response in patients with immune resistant solid tumors by promoting infiltration of effector immune cells into the tumor microenvironment.